Um zoológico em Machado de Assis : os animais na construção da filosofia machadiana - Silva, Leandro dos Santos (2019)
The animals have been constituted as the main metaphors on world literary even before the greats classicals fabulists and, in general, represent which is beyond human comprehesion. It has instigating the imagination of philosophers and writters in different areas and periods. There are many authors who use animal symbolism in their scripts. On Machado de Assis, creatures can be found at muliples texts of his compilation. Therefore, this dissertation has the objective of reflection, based an atitude philosophical-literary, on animal symbolism at Machado’s literature connecting with Machados’s philosophy, without carelessness of historical forces which intente the dissemination such symbols and metaphors throughout mankind evolution, as well external influences that helped to build Machado’s collection. For this reason, we use the reflection of zoocritic literary (MACIEL 2011, 2016; LESTEL, 2011; GARRARD, 2006) and the huge reflections in Machado’s critic (BOSI, 1982; CÂNDIDO, 2004; COUTINHO 1960; VERÍSSIMO 2003). In this research, the animal presence was analyzed in several spheres produced by Machado de Assis, from poetry to narrative, from romance to chronicle. The results acquired reveal that, at the first phase, next to lyricism and romanticism, the animal representation serves as an importante metaphor on scenary construction, altough not filled with romantic optmism, was filled with that values. After, the pessimism machadiano with irony and sarcasm goes demonstrating animal figures, doing the reader reflect, by the way of interpreter, through narrator or by the animal “speak” at his composition, about human been and his condition. Men always full of addictions and greed, give themselves up to the instincts like irrationals, in a totally paradoxal notion, making the animal figure important on the construction of his philosophy. From this resulte, we understanding to go back again at the classicals, using this new theory to understand not only the metaphors, but also his literary construction.